Pulmonary Vein Morphology in Patients Undergoing Catheter Ablation of Atrial Fibrillation - Barbora, Farkasová; Ondřej, Toman; David, Pospíšil; Monika, Míková; Nela, Hejtmánková; Anna, Zouharová; Lucie, Křikavová; Martin, Fiala; Milan, Sepši; Petr, Kala; Tomáš, Novotný (Cardiovascular engineering and technology, 2024)
PURPOSE: Variations in the anatomy of pulmonary veins can influence selection of approaches of atrial fibrillation catheter ablation. Therefore, preprocedural evaluation and knowledge of pulmonary veins anatomy is crucial for proper mapping and the successful ablation of atrial fibrillation. The aim of this observational study was to assess CT angiography scans and perform detailed analysis of pulmonary veins morphology in patients scheduled for catheter ablation of atrial fibrillation. METHODS: CT angiography was performed in 771 individuals (223 females, 548 males, mean age 58.4 ± 10.7 years). Pulmonary veins anatomy was evaluated using 3D models. The patterns used for evaluation included typical anatomy with four separate pulmonary veins, a common left ostium, and various types of accessory veins either alone or in combination with common left ostia. RESULTS: An anatomical variant with common left ostium was observed as the most prevalent anatomy (44%). The typical variant was observed in 34.8% of patients. Accessory pulmonary veins were observed predominantly on the right side. The prevalence of anatomical variants did not differ between sexes with the exception of the unclassifiable category U (4.4% vs. 9%, p < 0.05). CONCLUSIONS: Our study shows that a considerable number of atypical anatomies is present in patients undergoing AF catheter ablation. This knowledge may influence the choice of instrumentation. The data could be possibly helpful also in development of new ablation techniques.
Keywords: výsledek terapie; zobrazování trojrozměrné; Male; Aged; mužské pohlaví; senioři; Imaging, Three-Dimensional; Catheter Ablation; Pulmonary veins anatomy; CT angiography; Atrial Fibrillation; Pulmonary Veins; Treatment Outcome; Phlebography; Pulmonary veins morphology; lidé; Computed Tomography Angiography; ženské pohlaví; Humans; flebografie; prediktivní hodnota testů; venae pulmonales; Atrial fibrillation; CT angiografie; katetrizační ablace; Female; lidé středního věku; Predictive Value of Tests; fibrilace síní; Middle Aged